(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The better knowledge of the side effects of CPB and advancements in surgical instruments and techniques, coronary artery bypass grafting on the beating heart has grown in cardiac surgery. Off-pump coronary bypass grafting (OPCAB), will shifts the beating heart and restricts cardiac motion to expose the intended anastomosis site and entirely revascularize the heart. This can cause significant hemodynamic changes, myocardial ischemia and a loss in the performance of left ventricle. The aim of this study was to evaluate the hemodynamics of patients undergoing off-pump coronary artery bypass graft surgery.